A comparison of memory for homicide, non-homicidal violence, and positive life experiences - Woodworth, Michael; Porter, Stephen; Brinke, Leanne ten; Doucette, Naomi; Peace, Kristine; Campbell, Mary Ann (My University, 2009)
Defendants commonly claim amnesia for their criminal actions especially in cases involving extreme violence. While some claims are malingered or result from physiological factors, other cases may represent genuine partial or complete amnesia resulting from the psychological distress and/or extreme emotion associated with the perpetration of the crime. Fifty Canadian homicide offenders described their memories of their homicide, a non-homicide violent offense, and their most positive adulthood life experience. Self-reported and objective measures of memories for these events revealed that homicides were recalled with the greatest level of detail and sensory information. Although dissociative tendencies were associated with a self-reported memory loss, objective measures of memory quality did not reflect this perceived impairment, suggesting a failure of meta-memory. Recollections of positive life events were superior to those of non-homicidal violence, possibly due to greater impact and meaning attached to such experiences. Findings suggest that memory for homicide typically is enhanced by the powerful emotion associated with its perpetration.
Keywords: memory; trauma; homicide; violence; emotion; meta-memory